A new combination in Mcneillia (Caryophyllaceae) for the Italian flora - Bartolucci, Fabrizio; Conti, Fabio; Iamonico, Duilio; Guacchio, E. Del (Phytotaxa, 2014)
On the basis of DNA sequences of nrITS and plastid matK from 160 ingroup and 105 outgroup samples, Dillenberger & Kadereit (2014) reconstructed the phylogeny and the evolution of the relevant morphological characters of the genus Minuartia Linnaeus (1753: 89), to show that this genus is highly polyphyletic. A revised circumscription of Minuartia was proposed with the recognition of Cherleria Linnaeus (1753: 425), Eremogone Fenzl (1833: 13), Facchinia Reichenbach (1841: 63), Mononeuria Reichenbach (1841: 118), Rhodalsine Gay (1845: 25), Sabulina Reichenbach (1832: 24) and Triplateia Bartling (1830: 305), and recognition of new genera Mcneillia Dillenberger & Kadereit (2014: 83), Minuartiella Dillenberger & Kadereit (2014: 84) and Pseudocherleria Dillenberger & Kadereit (2014: 84).